Evaluation of Chemical and Physico-mechanical Properties of Ado-Ekiti Natural Moulding Sands for Foundry Applications - Shuaib-Babata, Y. L.; Abegunde, A. J.; Ambali, I. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2017)
Poor casting quality is associated with the use of locally available moulding sands without recourse to their suitability through adequate knowledge of their properties. The properties of some Ado-Ekiti moulding sands were therefore examined with the aim of establishing their suitability or otherwise for foundry applications. Some natural sand samples were obtained from Ureje, Omisanjana, Odo Ayo and Ogbese within Ado-Ekiti metropolis. Their chemical compositions were determined and analyzed using the X-ray fluorescence (XRF) spectrometer technique and atomic absorption spectrophotometer (AAS). The sands’ physico-mechanical properties were also examined in line with American Foundry Society (AFS) guidelines. The results of the chemical analysis indicated that the sands contained silica and aluminium oxide as their major constituents with values of 63.83 – 79.23% and 12.20 – 23.76% respectively. The Ureje, Omisanjana, Odo Ayo and Ogbese sands respectively possessed American Foundry-Men’s Society Grain Fineness Number (AFS-GFN): 63.27, 61.08, 66.98 and 61.12; clay content: 12, 13, 10 and 6%; moisture content: 12.04, 12.25, 12.23 and 11.92%; permeability 86.2, 87.5, 86.3 and 88.2%; flowability: 67.87, 68.50, 67.40 and 67.25%; green compression strength: 120.9, 63.6, 70.9 and 82.0 kN/m2; dry compression strength: 203.0, 101.8, 191.0 and 76.4 kN/m2. Each of the samples has refractoriness above 1200oC. The sands (except that of Ogbese sand) can be used naturally as core if the core length is short due to rapid decrease in the sands’ hot strength from 1100oC. These properties were found to fall within the required values for casting of most ferrous and non-ferrous metals, except that of Ogbese sand. Comparison of the results obtained from the studied sands’ properties with that of AFS mould sand properties for various types of castings revealed that the studied sands have the potential for use in sand casting process for metals like grey steel, light steels, brass, bronze and aluminum. Meanwhile, the properties of Ogbese natural sand can be improved with application of additive like bentonite to enhance its suitability for sand casting application.